Teletandem: integrating e-learning into the foreign language classroom - Suzi Marques Spatti Cavalari; Solange Aranha (Acta Scientiarum: Language and Culture, 2016)
This paper aims at describing the characteristics of a blended foreign language learning context in which a series of teletandem sessions has been integrated into the syllabus of an EFL course at UNESP (in São José do Rio Preto). It focuses on the changes that have been made in the implementation of teletandem practice so that it became a pedagogic activity that is embedded in an EFL course with a number of tasks to be performed and subject to the professor’s assessment. It is argued that such modifications have made it possible to characterize a new modality of teletandem in Brazil: institutional-integrated teletandem (Aranha & Cavalari, 2014). This new modality, as implemented at UNESP-Rio Preto, entails the presence of some constituent elements, such as preparation of participants, integration of tasks and of assessment.